A prospective clinical study of fistula in ano: comparing different treatment modalities in a tertiary care hospital - G. S. R., Hareesh; Nenavath, Siva Prasad Naik (International Surgery Journal, 2019)
Background: Fistula in ano is one of the common anorectal condition, which is easy to diagnose but difficult to manage because of post-operative complications like incontinence and recurrence. Also numerous procedures have been described for its treatment so as to individualize treatment options.The aim of the study was to assess the efficacy of different treatment modalities in fistula in ano. Methods: This is a prospective study carried out in a tertiary medical college hospital where 75 patients with fistula in ano are analysed for clinical features and surgical modalities compared. Results: Total 75 patients are studied. 82.70% patients presented with discharge in perianal region. Posterior fistulas are seen in 93.30% and anterior in 6.70% patients. 94.70% patients have low level fistula, 84% patients had simple fistula & 16% had complex fistula. 49.30% patients were treated with fistulectomy. 36.0% have undergone fistulotomy. 8.0% had LIFT and 6.7% had SETON. Recurrence is seen in 6.70% of patients.70.70% patients have stayed 4-6 days. Conclusions: Most of the fistulas are simple, posterior and low level fistulas. Fistulectomy is the most common procedure performed. Newer procedures like LIFT and Seton application show promising results with less complications.